Kandungan Kafein dan Karakteristik Morfologi Pucuk (Pekoe) dengan 3 Daun Muda (P+3) Enam Genotipe Teh - Budi Martono; Laba Udarno (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Caffeine plays an important role in determining a bitter flavor of tea. Different genotype and picking types cause differences in caffeine content and quality of tea. The research aimed to determine the caffeine content and morphological characteristics of shoots (peko) with 3 young leaves below (P+3) on several tea genotypes. The study was conducted at Tambi tea plantation and Laboratory of Testing, Center for Agro-based Industri (CABI), Bogor from April to June 2013. Caffeine was extracted using chloroform and measured at a wavelength of 276.5 nm. Caffeine analysis was carried out using shoots (peko) with 3 young leaves below (P + 3), which were arranged in a completely randomized design with 6 tea genotypes as treatments (Tbs 1 Tbs 2, RB 3, Kiara 8, Cin 143, and Hybrid) and replicated 4 times. Characterization on tea shoots was done by observing quantitative and qualitative characters. The results showed that genotypes had significant effect on caffeine content. RB 3 genotype had the highest caffeine content (3.58%) followed by Cin 143 genotype (3.43%). Based on caffeine content, Tbs 1 and Tbs 2 are promising genotypes with better quality than RB 3 and Cin 143. The diversity among genotypes revealed by shape, base, edges, and the tips of the leaves; the upper surface of leaves, leaf color, feathers on shoots (peko), leaf length and width characters, the ratio of the length and width of leaf, petiole length, number of leaf bones, flesh thick leaves, and shoots (peko) length. Moreover, caffeine content was negatively correlated with the ratio of the length and width of leaf.